(untitled) (Sociologisk Forskning, 2007)
Meanings of overweight In societal discourses overweight is defined as a growing individual and a social problem leading to sickness and disability, mental distress, increased use of health care and reduced economic productivity. A strong normative pressure is directed at the overweight but relatively few succeed in reducing their weight. Therefore, the overweight need to manage a double stigma; the overweight body per se and their inability to conform to norms about bodyweight. This article investigates how individuals present their overweight to their social environment. Empirical data was collected as part of an evaluation study of a keep-fit project directed at home-care staff. Qualitative interviews were conducted with 49 participants and 30 of them had either tried or were trying to reduce their weight. The analysis shows that the informants presented a divided self consisting of a biological body, with its own drives, and a mind that is aware of the body and its social meanings. They portrayed their lives as a battle between these two sides. Their presentations of the divided self can be analysed as a defence of their social selves. The overweight can account for the kilos by blaming the biological drives, which leaves the core of themselves – their minds – unblemished. They can express an intention to loose weight and thereby conform to norms about bodyweight. When they fail to loose weight, the responsibility can be attributed to the unruly body.